2023
DOI: 10.1007/s00784-023-05133-9
|View full text |Cite
|
Sign up to set email alerts
|

A new CAD/CAM tooth mobility simulating model for dental in vitro investigations

Abstract: Objectives To validate a new tooth mobility simulating in vitro model for biomechanical tests of dental appliances and restorations. Material and methods Load-deflection curves for teeth in CAD/CAM models (n = 10/group, 6 teeth/model) of the anterior segment of a lower jaw with either low tooth mobility (LM) or high tooth mobility (HM) were recorded with a universal testing device and a Periotest device. All teeth were tested before and after different ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…By varying the material properties of the periodontal ligament, it was possible to achieve low (1 µm/N), medium (2 µm/N), or high (3 µm/N) TR values in the vertical direction. Previous studies [18,19] have indicated that the ratio between the horizontal and vertical TR should lie between three and four. Detailed information about the simulated TR is presented in Table 2.…”
Section: Tooth Resiliencementioning
confidence: 91%
“…By varying the material properties of the periodontal ligament, it was possible to achieve low (1 µm/N), medium (2 µm/N), or high (3 µm/N) TR values in the vertical direction. Previous studies [18,19] have indicated that the ratio between the horizontal and vertical TR should lie between three and four. Detailed information about the simulated TR is presented in Table 2.…”
Section: Tooth Resiliencementioning
confidence: 91%